Who were the first Christians? : dismantling the urban thesis - Robinson, Thomas A. (Thomas Arthur), 1951- (New York : Oxford University Press, 2017)
Thomas Robinson argues that popular views of early Christian growth - one concentrated in urban environments - would nearly saturate every urban area of the entire Roman Empire with Christians, leaving no room for Jews or pagans. It is a scenario that simply does not work. But where does the solution lie? Robinson argues that the urban thesis is defective, and the neglected countryside must now be considered in any reconstruction of early Christian growth.
1. Introduction: Must Historians Count? -- 2. The "Urban" Thesis -- 3. Counting Romans and Christians -- 4. Counting the Jewish Population -- 5. Urban and Rural Relationships -- 6. Supposed Barriers to Christian Success in the Countryside -- 7. The Pre-Constantinian Evidence -- 8. Dismissing the Evidence of Christianity in the Countryside -- 9. The Country Bishop -- 10. Conclusion -- Appendix A. The Numbers According to Ramsay MacMullen -- Appendix B. The Numbers According to Rodney Stark
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: prvotní církev; rané křesťanství; early Christianity; primitive church; monografie; e-knihy online; monographs; e-books online